Analisis Risiko Kesehatan Lingkungan Permukiman Pedesaan Berbasis Indeks Risiko Kesehatan Lingkungan (IRKL) di Desa Karangmangu, Baturraden - Saumi Anggit Musofi; Iqbal Ardiansyah (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
Community sanitation and hygiene, as well as household sanitation and hygiene, are factors that influence public health. Poor environmental sanitation conditions and hygiene practices can increase the risk of environment-related diseases. The purpose of this study was to determine the status of community sanitation and hygiene and household sanitation and hygiene, as well as the relationship between the two, in Karangmangu Village, Baturraden Subdistrict, Banyumas Regency. The study employed an observational design with a quantitative descriptive approach. The study population consisted of 208 residents, with a sample of 136 respondents selected using purposive sampling. Data were collected through interviews and observations. The results of the Chi-Square test indicated a significant association between household sanitation and community sanitation, with a p-value of 0.000 (<0.05). The results of the Spearman’s rho test showed a very strong relationship between household sanitation hygiene and community sanitation hygiene, with a correlation coefficient of 0.990 and p = 0.000 (<0.05). The Spearman correlation coefficient of 0.990 indicates that residents’ sanitation hygiene has a very strong relationship with community sanitation hygiene. This high correlation is likely due to the fact that both variables are assessed using the Environmental Health Risk Index (IRKL), which includes several interrelated assessment components, such as clean water supply, basic sanitation, waste management, and hygiene practices. Thus, improvements in residents’ hygiene practices are generally followed by improvements in settlement sanitation conditions, and vice versa. This interdependence results in a very strong relationship between the two variables. In addition to being influenced by the commonality of several assessment components within the IRKL, the high correlation coefficient also indicates that residents’ hygiene practices and settlement sanitation conditions are two mutually reinforcing aspects in creating a healthy home environment. Environmental health risk components that remain major issues include wastewater management, waste management, indoor air quality, and the presence of disease vectors. The study’s conclusions indicate a very strong relationship between residents’ hygiene and sanitation practices and the sanitation conditions of the residential area. Recommendations: The community is encouraged to improve environmental sanitation management, vector control, and clean and healthy living behaviors to reduce environmental health risks.